Novel Target Exploration from Hypothetical Proteins of Klebsiella pneumoniae MGH 78578 Reveals a Protein Involved in Host-Pathogen Interaction - Pranavathiyani, G.; Prava, Jyoti; Rajeev, Athira C.; Pan, Archana (Frontiers in Cellular and Infection Microbiology, 2020)
The opportunistic pathogen Klebsiella pneumoniae is a causative agent of several hospital-acquired infections. It has become resistant to a wide range of currently available antibiotics leading to high mortality rates among patients thereby demanding a novel therapeutic intervention for treating such infections. Using a series of in silico analyses the present study aims to explore novel drug/vaccine candidates from the hypothetical proteins of K. pneumoniae. A total of 540 proteins were found to be hypothetical in this organism. Analysis of these 540 hypothetical proteins revealed that 30 proteins were pathogen-specific and essential for the pathogen survival. Motifs/domain family analysis, similarity search against known proteins, gene ontology and protein-protein interaction analysis of the shortlisted 30 proteins led to functional assignment for 17 proteins. They catalogued majorly into enzymes, lipoproteins, stress-induced proteins, transporters and other proteins (viz., two-component proteins, skeletal proteins and toxins). Among the annotated proteins, 16 proteins, located in cytoplasm, periplasm and inner membrane, were considered as potential drug targets, and one extracellular protein was considered as a vaccine candidate. Druggabality analysis indicated that the identified 17 drug/vaccine candidates were ‘novel’. Further, host-pathogen interaction analysis of these identified target candidates revealed a betaine/carnitine/choline transporters (BCCT) family protein showing interactions with five host proteins. Structure prediction and validation were carried out for this protein, which could aid in structure-based inhibitor design.